LEAD US, LORD, a collection of African hymns. Compiled by Howard S. Olson, Augsburg Publishing House, U.S.A., 1977, pp. 22, $1.50. - Jones, A. M. (International Library of African Music, 1980)
pages: 134-135
Keywords: African Music